Orientasi Modal Sosial dan Kewirausahaan dalam Pengembangan Wisata Lokal-Kalimantan Barat - Usman; Jewarut, Siprianus; Kusnanto (Sekolah Tinggi Ilmu Ekonomi AMM, 2024)
Local tourism development in the Setanga Lestari area requires an integrated approach between social capital and entrepreneurship. Social capital, which includes social networks, trust and norms that exist in society, plays an important role in building cooperation between stakeholders, both government, local communities and business actors. On the other hand, entrepreneurship is a driving force for innovation and competitiveness in exploiting local potential in a sustainable manner. This research aims to analyze how social capital orientation can strengthen entrepreneurial activities in the context of local tourism development. By focusing on aspects of social relations and entrepreneurial innovation, this research explores the role of social capital in improving economic, cultural and environmental sustainability in the Setaga Lestari tourist area. In addition, this research also explores how social capital supports the creation of more inclusive and sustainable local business networks. The research results show that developing the local tourism component of Setanga Lestari not only requires adequate business skills, but also optimal use of existing social networks and collaborations. in society. Strengthening social capital and entrepreneurship can increase the added value of local tourism products, expand market access, and create wider job opportunities for local communities. Thus, it is hoped that this approach can be an effective strategy in creating a sustainable and inclusive tourism ecosystem in Setanga Lestari.